Incorporation of an extract rich in rosmarinic acid into cupcakes: Influence on the sugars and total carbohydrates composition - Caleja, Cristina (2018)
Currently, the food industry is focused on replacing synthetic additives with natural ingredients. Natural extracts obtained from plants have emerged as possible alternatives to synthetic preservatives, namely antioxidants [1]. Some dairy, meat and bakery products have been developed incorporating extracts of aromatic plants, spices or fruits, which have antioxidant properties [2-4]. In this work, we intend to prove the efficacy of an extract rich in rosmarinic acid as a natural preservative in cupcakes and compare these results to a synthetic additive (potassium sorbate, E202), which is normally used in pastry products. The extract of Melissa officina/is L. (lemon balm) was obtained by performing an ultrasound-assisted extraction with ethanol. After evaluation of its antioxidant (free radical scavenging activity, EC50 = 79 ± 2 J.Jg I ml; reducing power EC50 = 49 ± 1 J.Jg I ml) and antimicrobial (against 8 bacteria and 8 fungi contaminants) properties, and confirmation of toxicity absence (in a non-tumor cell line), the extract enriched in rosmarinic acid was incorporated into the cupcakes. Its effect was compared to E202 and to a control sample (cupcakes without additives) immediately after incorporation and in the 3n;l and 5th day of storage, protected from light at room temperature. The results showed that both natural (extract enriched in rosmarinic acid) and synthetic (E202) additives, did not cause significant changes in the nutritional composition of cupcakes (fat, protein and carbohydrate contents), when compared with the control sample. Free sugars were also determined by high performance liquid chromatography coupled to a refractive index detector (HPLC-RI), which indicated sucrose and glucose as the most abundant sugars in all samples. These molecules did not undergo any changes with the addition of the additives as compared to the control sample. The results obtained demonstrate that the presence of rosmarinic acid does not influence sugars and total carbohydrates content of cupcakes and may be used in the development of new pastry and bakery products, replacing synthetic preservatives and improving the functional properties of the food.